2021
DOI: 10.1016/j.celrep.2020.108628
|View full text |Cite
|
Sign up to set email alerts
|

MDA5 Governs the Innate Immune Response to SARS-CoV-2 in Lung Epithelial Cells

Abstract: Highlights d SARS-CoV-2 replication induces a delayed IFN response in lung epithelial cells d MDA5 and LGP2 are the major sensors recognizing SARS-CoV-2 infection d Viral intermediates activate the IFN response through MDA5mediated sensing d IRF3, IRF5, and NF-kB/p65 are required for the IFN response induced by SARS-CoV-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
280
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(313 citation statements)
references
References 65 publications
32
280
0
1
Order By: Relevance
“…Both MDA5 and RIG-I may displace viral proteins pre-bound to dsRNA in a manner dependent on their ATP hydrolysis, thus exerting a MAVS-IFN-independent broad-spectrum antiviral role (Sindbis, yellow fever, Coxsackie B, Sendai, influenza A, and human parainfluenza 3 viruses) 18 . During the submission of this manuscript, a study showed an important anti-SARS-CoV-2 role of MDA5 that is consistent with our results, however dispensable function of RIG-I in limiting SARS-CoV-2 infection 19 . This discrepancy could be due to a difference in the cell line and gene knockout method.…”
Section: Resultssupporting
confidence: 90%
“…Both MDA5 and RIG-I may displace viral proteins pre-bound to dsRNA in a manner dependent on their ATP hydrolysis, thus exerting a MAVS-IFN-independent broad-spectrum antiviral role (Sindbis, yellow fever, Coxsackie B, Sendai, influenza A, and human parainfluenza 3 viruses) 18 . During the submission of this manuscript, a study showed an important anti-SARS-CoV-2 role of MDA5 that is consistent with our results, however dispensable function of RIG-I in limiting SARS-CoV-2 infection 19 . This discrepancy could be due to a difference in the cell line and gene knockout method.…”
Section: Resultssupporting
confidence: 90%
“…We also found that IFIH1 (NM_022168.4), that encodes for Melanoma Differentiation-Associated Protein 5 (MDA5) is significantly up-regulated in the SARS-CoV-2 infected samples (Supplementary Table S7, P-adjusted = 7.46e-137). This is in line with findings indicating that the IFN response upon SARS-CoV-2 infection is primarily regulated by MDA5 (Yin et al, 2021). Since ADAR1 is known to prevent MDA5 from sensing dsRNA (Liddicoat et al, 2015), this result strengthening the conclusion that ADAR1 is largely involves in the immune response following SARS-CoV-2.…”
Section: Sars Cov-2 Infection Results In An Extensive A-to-i Hyper Rna Editing and Upregulation Of Adar1 Enzymesupporting
confidence: 88%
“…In this study, consistent with several recent reports 1921 , we identified Calu-3 cells as a suitable model system for the study of innate immune responses to SARS-CoV-2 infection in vitro .These adenocarcinoma-derived lung epithelial cells expressed key proteins of RNA- and DNA-sensing pathways, responded to stimulation with type I IFN, and were highly infected by SARS-CoV-2. Importantly, SARS-CoV-2 induced transcription of the genes encoding type I and III IFNs, as well as pro-inflammatory cytokines in these cells.…”
Section: Discussionsupporting
confidence: 89%
“…In Calu-3 cells, RIG-I was largely dispensable for the antiviral cytokine response to infection. While our study was in preparation, other manuscripts reported MDA5 as the cellular sensor that recognises SARS-CoV-2 infection 19,20 . These reports included both siRNA-mediated knockdown and genetic ablation in Calu-3 cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation